The Influences of Iron Ore Tailings as Fine Aggregate on the Strength of Ultra-High Performance Concrete - Zhigang Zhu; Beixing Li; Mingkai Zhou (Advances in Materials Science and Engineering)
The present study looks for the feasibility of preparing UHPC with iron ore tailings (IOT for short) as fine aggregate. To enhance outstanding high performances, some influences on UHPC mortars were investigated such as different kinds of sands, different mix ratio of sands, and different largest particle size of fine aggregate. The results show that IOT have negligible poorer aggregate performance than silica sands but better than river sands. The strength of UHPC reaches the highest point when silica sands were instead 60% by IOT. As the largest particle size of fine aggregate is decreasing, the strength and frost resistance of UHPC were improved, but the liquidity was decreased. Micropowder of IOT affects the strength and the optimal content was 4%.